Experimental Investigation on WAAM-based Functional Wear-Resistant Bimetallic Part (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Wire Arc Additive Manufacturing (WAAM) coupled with robotic systems enhances the fabrication of large-scale and complex metallic components utilized across various sectors such as aerospace, defense, maritime and automotive. Functional wear-resistant bimetallic parts are among the metallic components which can be produced via this manufacturing technology. Traditionally, manufacturing wear-resistant components involves cladding hard-facing materials onto a base metal, a process that is often complex, costly, and time-intensive. This paper proposes the adoption of the WAAM process for creating functional wear-resistant bimetallic part using hard-facing solid welding wire, aiming to improve wear resistance. The performance of wear-resistant bimetallic parts is significantly influenced by the selected multi-material, hardness distribution, interface morphology, and bond strength at the interface. In this study, the wear-resistant bimetallic part was built through the deposition of hard-facing welding wire onto the deposited 316L Si austenitic stainless steel. After the initial visual inspection and digital radiographic tests, hardness distribution was examined along with the macro and microstructural evaluations. In the subsequent analyses, tensile and Charpy V-notch tests were conducted using the extracted samples from the manufactured bimetallic part. As a result, the characterization and mechanical response of the robotic WAAM-based manufactured functional wear-resistant bimetallic part have been revealed.
Keywords: WAAM-based manufacturing; Hard-facing welding wire; Bimetallic Wear-resistant Component; Bimetallic Interface